2022
DOI: 10.1136/bmjopen-2021-058531
|View full text |Cite
|
Sign up to set email alerts
|

Expectations, end-of-life fears and end-of-life communication among palliative patients with cancer and caregivers: a cross-sectional study

Abstract: ObjectivesDuring serious illness, open communication with caregivers can ensure high-quality care. Without end-of-life communication, caregivers may become surrogates and decision-makers without knowing the patient’s preferences. However, expectations and fears may influence the initiation of communication. The present study investigates differences between palliative patients with cancer and caregivers regarding expectations of end-of-life communication, end-of-life fears and experiences with end-of-life comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Being diagnosed with advanced cancer brings anxiety and uncertainty with the anticipation of suffering and fear of death. 18 , 19 The patients want to participate in their care process with necessary information for the best decisions. They hope to be prepared for their death making certain arrangements beforehand.…”
Section: Discussionmentioning
confidence: 99%
“…Being diagnosed with advanced cancer brings anxiety and uncertainty with the anticipation of suffering and fear of death. 18 , 19 The patients want to participate in their care process with necessary information for the best decisions. They hope to be prepared for their death making certain arrangements beforehand.…”
Section: Discussionmentioning
confidence: 99%
“…Open communication with a seriously ill person refers to honest and straightforward conversations about illness and death, including the verbalization of associated fears and emotions [ 7 ]. Open communication about illness and death between patients and relatives can positively affect the well-being of relatives during caregiving, as it has been shown to be associated with reduced caregiver burden [ 8 , 9 ] and increased personal relief [ 10 ]. Conversely, research has shown that poor communication during the caregiving period is associated with higher levels of depression [ 11 ], increased feelings of guilt and regret [ 12 ], and more complicated grief experiences [ 11 , 13 ] among relatives during the bereavement period.…”
Section: Introductionmentioning
confidence: 99%
“…Open communication with a seriously ill person refers to honest and straightforward conversations about illness and death, including the verbalization of associated fears and emotions (7). Open communication about illness and death between patients and relatives can positively affect the well-being of relatives during caregiving, as it has been shown to be associated with reduced caregiver burden (8, 9) and increased personal relief (10). Conversely, research has shown that poor communication during the caregiving period is associated with higher levels of depression (11), increased feelings of guilt and regret (12), and more complicated grief experiences (11,13) among relatives during the bereavement period.…”
Section: Introductionmentioning
confidence: 99%